The Intriguing Case of the One‐Photon and Two‐Photon Absorption of a Prototypical Symmetric Squaraine: Comparison of TDDFT and Wave‐Function Methods. Issue 9 (12th July 2019) - Avila Ferrer, Francisco J.; Angeli, Celestino; Cerezo, Javier; Coriani, Sonia; Ferretti, Alessandro; Santoro, Fabrizio
Abstract: We face the challenging description of the excited states responsible for one photon (OPA) and two photon (TPA) absorption in squaraine dyes, adopting both time‐dependent density functional theory and a large variety of post Hartree Fock methods, including coupled cluster and adiabatic diagrammatic construction methods (ADC, to the second and third order), symmetry adapted cluster configuration interaction (CI), CASSCF including second‐order perturbative corrections (PT2) with standard CASPT2 recipe and according to n‐electron valence PT2 (NEVPT2) approach, and an additional multireference CI with PT2 corrections (CI‐MRPT2). We selected a small prototypical symmetric squaraine dye for which these accurate computations are feasible and experimental data are available. We show that while all methods reasonably reproduce the OPA spectrum, an acceptable description and assignment of the states responsible for TPA is only possible through ADC(3) and multireference calculations, due to the strong involvement of double‐excitations. The nature of ground state and OPA and TPA states is investigated with a rigorous reading of the CASSCF wavefunctions in terms of localized molecular orbitals on the donor and acceptor fragments, showing that these states arise from a balance of many different contributions including biradical configurations, local excitations and charge‐transfer states where both side aromatic rings and the carbonyls of the squarylium moiety act as donors. Abstract : Single and double excitations . We performed a computational study of the excited states of a symmetric squaraine dye with TD‐DFT and post‐HF methods. A balanced treatment of single and double excitations is necessary for a coherent description of one‐photon and two‐photon absorption.